Rebuilding Afghanistan in times of crisis a global response - Awotona, Adenrele A. (Routledge research in planning and urban design, 2019)
Rebuilding Afghanistan in Times of Crisis provides academics and researchers interested in planning, urbanism and conflict studies with a multidisciplinary, international assessment of the reconstruction and foreign aid efforts in Afghanistan. The book draws together expert contributions from countries across three continents, Asia, Europe and North America, which have provided external aid to Afghanistan. Using international, regional and local approaches it highlights the vital importance of rebuilding sustainable communities in the midst of ongoing uncertainties. It explores the efficacy of external aid; challenges faced; the response of multilateral international agencies; the role of women in the reconstruction process; and community-based natural disaster risk management strategies. Finally, it looks at the lessons learned in the conflict reconstruction process to better prepare the country for future potential human, economic, infrastructural and institutional vulnerabilities